2019
DOI: 10.1016/j.molliq.2019.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, traction and tribofilm formation properties of three octanoate-, laurate- and palmitate-anion based ionic liquids

Abstract: Three new ionic liquids with different anions and the same cation were synthesized from fatty acids through a metathesis reaction. All the ionic liquids were identified via NMR and FTIR and several properties (density, viscosity, thermal, and environmental) were measured. Traction tests were performed under different entrainment speeds (10-2000 mm/s), at slide-roll ratio (SRR) of 50% and 30 N-load, and at different temperatures (40, 60, 80 and 100 ºC) using a mini-traction machine (MTM). Tribofilm formation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 41 publications
5
23
0
Order By: Relevance
“…In addition, Yu et al [63] observed that longer alkyl chain makes the salt more viscous because of an increase in van der Waals interactions. However, both properties decrease in this research with the increase of the alkyl chain length of the anion, similarly to other FAILs employed in previous research works [64][65][66][67]. The differences in viscosity behavior could be explained in a similar way that what happen with surface tension [46].…”
Section: Density Viscosity and Thermal Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, Yu et al [63] observed that longer alkyl chain makes the salt more viscous because of an increase in van der Waals interactions. However, both properties decrease in this research with the increase of the alkyl chain length of the anion, similarly to other FAILs employed in previous research works [64][65][66][67]. The differences in viscosity behavior could be explained in a similar way that what happen with surface tension [46].…”
Section: Density Viscosity and Thermal Propertiessupporting
confidence: 80%
“…Besides, the onset of temperature degradation was between 165 and 180 ºC (Table 3). Comparing these mentioned results with that of two ILs containing the same anions obtained in a previous research, it was found that thermogravimetric results are almost the same until T 50% (around 200 ºC) [64].…”
Section: Density Viscosity and Thermal Propertiessupporting
confidence: 70%
“…All these reagents were provided by Sigma-Aldrich S.A and used without further purification. These FAILs were obtained through a salt metathesis reaction, which is explained in a previous research work [53].…”
Section: Surfaces and Ionic Liquidsmentioning
confidence: 99%
“…The fatty acid-based ionic liquids (FAILs) were synthesized by means of a salt metathesis reaction according to Battez et al [31]. The details related to their identification through 1 H and 13 C NMR and FTIR analyses can also be found in Battez et al [31] and Blanco et al [32].…”
Section: Fatty Acid-based Ionic Liquidsmentioning
confidence: 99%
“…The fatty acid-based ionic liquids (FAILs) were synthesized by means of a salt metathesis reaction according to Battez et al [31]. The details related to their identification through 1 H and 13 C NMR and FTIR analyses can also be found in Battez et al [31] and Blanco et al [32]. Methyltrioctylammonium bromide ionic liquid ( 97%) was employed as cation precursor and natural fatty acids: hexanoic ( 98%), octanoic ( 98%), lauric ( 98%), palmitic ( 98%), stearic ( 98%) and oleic ( 95%) acids were used as anion precursors.…”
Section: Fatty Acid-based Ionic Liquidsmentioning
confidence: 99%